2012
DOI: 10.1103/physrevc.85.064609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neutron richness on the behavior of nuclear systems at intermediate energies

Abstract: We discuss results concerning the behavior of hot nuclear sources formed in 40 ,48Ca+40 ,48Ca reactions at 25 MeV/nucleon. A correlation between the neutron-to-proton ratio of the total systems and heavy residue production is found. This correlation underlines the strong role played by the neutron-to-proton ratio degree of freedom on the behavior of hot nuclei at intermediate energies. Comparisons of our data with Constrained Molecular Dynamics calculations confirm that a moderately stiff behavior of the symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…It has been shown [98,99] that different reaction mechanisms from isospin fractionation in the disintegrating system to isospin migration to the low-density neck region , as well as cluster correations, depend on the density-dependence of the symmetry energy [96,100,101].…”
Section: A Heavy-ion Collisions At Low Densitiesmentioning
confidence: 99%
“…It has been shown [98,99] that different reaction mechanisms from isospin fractionation in the disintegrating system to isospin migration to the low-density neck region , as well as cluster correations, depend on the density-dependence of the symmetry energy [96,100,101].…”
Section: A Heavy-ion Collisions At Low Densitiesmentioning
confidence: 99%
“…and experimental efforts. Up to now, both the statistical and dynamical approaches can equally well describe many observables in intermediate energy HICs, such as charge distributions, mean kinetic energies of the emitted fragments and so on, but each of them fail to describe some observables predicted by others, such as the isotope yields, isoscaling, isospin diffusion, bimodality [1,2,3,4,5,6,7,8,9,10,11,12,13,14]. It turns out that this problem is still open and the situation is very complicated.…”
mentioning
confidence: 99%
“…Previous study in reference [15] has shown there is interplay between the binary/ternary break-up (fusion-fission) modes and multi-fragmentation mode, especially for the low-intermediate energy HICs (20-40MeV/nucleon). The binary and ternary break-up [13,14,15,16,17,18,19] modes are mainly related to a slow process [20,21] which can also be described in the statistical way, and multi-fragmentation break-up mode is related to a fast process which can be described in dynamical way. Special attentions have been paid to semi-peripheral collisions at low-intermediate energy for further understanding the fragmentation mechanism, because it is the best way to study the interplay between fusion-fission and multi-fragmentation [17,18,19,22,23,29,24,25] process.…”
mentioning
confidence: 99%
“…For each of the three forms of the symmetry energy, approximately 350,000 events were simulated over a triangular impact parameter range from 0 to 12 fm. Lastly, it is worth noting that the CoMD model has been successful in both describing complex heavy-ion collision dynamics over long timescales (including dynamical fission) and providing constraints on E sym (ρ) through comparison with experimental data [21,[48][49][50].…”
mentioning
confidence: 99%
“…The sensitivity of N/Z with breakup time to L can be understood in terms of an initial isospin equilibration followed by a competition of the dinuclear PLF to "fuse" (producing a single PLF) rather than break up into the Z H and Z L fragments [49,50]. The dinuclear system is formed during the projectile-target interaction.…”
mentioning
confidence: 99%